What bridges the gap between self-harm and suicidality? The role of forgiveness, resilience and attachment. (30th July 2016) - Nagra, Gurmokh S.; Lin, Ashleigh; Upthegrove, Rachel
Abstract: Self-harm is the most robust risk for completed suicide. There is a lack of understanding of why some people who self-harm escalate to suicidal behaviour when others do not. Psychological factors such as attachment, self-forgiveness and self-appraisal may be important. To determine whether factors from the Interpersonal Theory and Schematic Appraisals models are useful to identify suicidal behaviour in populations that self-harm. Specifically we investigate whether resilience factors of secure attachment, self-forgiveness and positive self-appraisals significantly influence suicidality in people who self-harm. A cross-sectional online study of 323 participants recruited from self-harm support forum. Validated self-report measures were used to assess appraisals, relationships, self-forgiveness, attachment style, suicidality and self-harm. Emotion coping and support seeking self-appraisals and self-forgiveness were negatively associated with suicidality in participants with a history of self-harm. Dismissing attachment was positively associated with suicidality. The perceived ability to cope with emotions, the perceived ability to gain support and self-forgiveness may protect against suicide in people who self-harm. Conversely the presence of dismissing attachment may increase the risk of suicidality. Findings provide therapeutic targets to reduce risk of suicidality in this high risk group. Highlights: Psychological correlates of suicidality were examined in self-harm. Emotion coping, self-forgiveness, support seeking and positive self-appraisals were associated with a reduced risk of suicidality. Suicidality was associated with higher levels of dismissing attachment. Implications are for risk assessment in patients with a history of self-harm and suggests targets for psychological intervention.